High flow nasal oxygen versus mechanical ventilation as initial respirator support in severe COVID-19 ARDS at Groote Schuur Hospital : a propensity score analysis - Van Den Berg, Robert William (Department of Medicine, 2025)
OBJECTIVE: The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) pandemic placed an unprecendented burden on global health care resources, and on intensive care unit (ICU) resources in particular. Due to ICU resource limitations, high flow nasal oxygen (HFNO), a novel ventilation strategy, was implemented as an alternative to mechanical ventilation (MV) at Groote Schuur Hospital in Cape Town, South Africa, during the first COVID wave. Patient received MV if HFNO failed. The purpose of this study was to compare outcomes of this “HFNO first” strategy to a “MV first” strategy. METHODS: This was a secondary analysis of two propsective cohort studies conducted during the COVID first wave at Groote Schuur Hospital. Propensity score matching was used to compare outcomes between HFNO as initial ventilation strategy and MV as first-line therapy. Eligible patients were adults (> 18 years) with severe respiratory failure and confirmed COVID-19 pneumonia. The primary endpoint was survival to hospital discharge and secondary analysis assessed duration of respiratory support. RESULTS: After propensity score matching, 110 patients (55 in each group) were included in the final analysis. Survival to hospital discharge was significantly higher in patients treated with HFNO first compared to MV first; 31/55 (56%) versus 17/55 (31%), p=0.007. After adjustment for other covariates, the “HFNO first” group had a 71% increased chance of survival to hospital discharge when compared to the “MV first” group; OR=0.28, 95% CI [0.13 – 0.63], p=0.0018. There was a non-significant trend in patients treated with HFNO group requiring less time on respiratory support (p= 0.06). CONCLUSION: This study supports the evidence for the use of HFNO as an initial ventilation strategy for patients with COVID-19-related acute respiratory distress syndrome (ARDS). Survival rates in the “HFNO first” cohort were significantly higher, even in those that subsequently required ventilation, compared to the “MV first” strategy. This study adds important evidence to the debate on the potential benefits and harms of HFNO as well as highlighting its advantages in a resource-constrained setting. The efficacy and implementation of HFNO as an initial ventilation strategy require further investigation. The “HFNO first” strategy employed at Groote Schuur Hospital in the first wave of the COVID-19 pandemic demonstrated a markedly higher survival rates. This suggests that HFNO is highly effective as an initial ventilation strategy in COVID-19 ARDS in a resource-limited setting